2013
DOI: 10.3136/fstr.19.765
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Heat Transfer Modeling in Japanese Pears (Pyrus pyrifolia) during Tempering

Abstract: This research was conducted to study heat transfer in Japanese pears based on their exact geometry as measured by a 3D laser scanner. Some of the thermal properties of three cultivars of Japanese pear (Pyrus pyrifolia) were measured, boundary conditions were defined and heat transfer modeling was conducted using COMSOL Multiphysics 4.2a software based on the finite element method. The thermal conductivity of each examined cultivar was estimated from the model and found to be 0.66 ± 0.01, 0.56 ± 0.09 and 0.58 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The 3D geometry, volume and density The 3D image of each pear was obtained using NextEngine 3D Laser Scanner (NextEngine Inc.) with standard speed (SD) settings (about 6.45 10 8 points m 2 ) and macro range settings with 0.0001 m accuracy. Other configurations were set as one family with 360°positioning and 7 divisions followed by two scan families with single positioning in order to scan the top and bottom of the fruit (E. Rezagah et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D geometry, volume and density The 3D image of each pear was obtained using NextEngine 3D Laser Scanner (NextEngine Inc.) with standard speed (SD) settings (about 6.45 10 8 points m 2 ) and macro range settings with 0.0001 m accuracy. Other configurations were set as one family with 360°positioning and 7 divisions followed by two scan families with single positioning in order to scan the top and bottom of the fruit (E. Rezagah et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of the volume measurements was examined by measuring the diameter of a sphere-shaped object with 5 replications by a digital caliper with accuracy of 0.0002 m (Digimatic caliper, Mitutoyo Co., Japan), calculating the sphere's volume knowing its radius and comparing it with the volume obtained from the 3D laser scanner (E. Rezagah et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated that the size of the fruit is the most important parameter in the heating rate whilst fruit thermal conductivity has a little effect in the transient behaviour of heating process. Experimental and Computational Fluid Dynamics (CFD) modelling studies were carried out by Rezagah et al [11] in order to describe the transient heat transfer of three several kinds of Japanese pears during tempering. In this study, a 3-D laser scanner was utilized for obtain a 3-D geometry of a pear whereas T type copper-constantan thermocouples were used in order to monitoring the transient temperatures inside the peers during heating.…”
Section: Bibliographical Reviewmentioning
confidence: 99%